METODE MEMAHAMI HADIS-HADIS MUKHTALIF (KONTRADIKTIF) - Jamaluddin, Jamaluddin (Fakultas Agama Islam, 2021)
This paper describes the method (method) of resolving maqbul hadiths that contradict each other (mukhtalif), namely sahih or hasan traditions which outwardly appear to contradict other authentic or hasan traditions. However, the aims of these traditions are not contradictory, because in principle they can be resolved by: First, compromising, namely trying to collect the two, until the resistance is lost. Second, Nasakh is looking for which of the two hadiths came first, and which came later. So the hadith that came first should be narrated by the hadith that came later. Third, Tarjih, which is conducting research on which hadiths are strong, both sanad and matan, to be interpreted. A strong hadith is called a rajih hadith, while a tarjih hadith is called a marjuh.